2022
DOI: 10.1097/aci.0000000000000821
|View full text |Cite
|
Sign up to set email alerts
|

Drug allergy desensitization is not a unique recipe

Abstract: Purpose of reviewDrug desensitization is the only therapeutic option for patients with drug allergies who need to receive the drugs they are allergic to, and it is especially critical in patients with an urgent need for chemotherapy, biologics, or antibiotics, where equally effective alternatives might not be available. However, drug desensitization is not a cookbook where anyone with no experience or specific training can find a general recipe. This review article will approach the singularities that make per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 55 publications
0
13
0
3
Order By: Relevance
“…2 As for the temporary nature of RDD, these findings are compatible with real-life experience, where chemotherapy-allergic patients receiving chemotherapy every 2-3 weeks need desensitization for every administration. 2,298 In contrast, antibiotic-allergic patients will usually receive continuous exposure to an antibiotic for a continuous course and, generally, will only need desensitization for the first dose of the course. 2,67,298 The exact duration of the desensitized state is unknown and might be influenced by multiple factors.…”
Section: Rapid Drug Desensitizationmentioning
confidence: 99%
See 4 more Smart Citations
“…2 As for the temporary nature of RDD, these findings are compatible with real-life experience, where chemotherapy-allergic patients receiving chemotherapy every 2-3 weeks need desensitization for every administration. 2,298 In contrast, antibiotic-allergic patients will usually receive continuous exposure to an antibiotic for a continuous course and, generally, will only need desensitization for the first dose of the course. 2,67,298 The exact duration of the desensitized state is unknown and might be influenced by multiple factors.…”
Section: Rapid Drug Desensitizationmentioning
confidence: 99%
“…2,298 In contrast, antibiotic-allergic patients will usually receive continuous exposure to an antibiotic for a continuous course and, generally, will only need desensitization for the first dose of the course. 2,67,298 The exact duration of the desensitized state is unknown and might be influenced by multiple factors. Shalit et al found that desensitized mast cells can be activated after 24 hours 72,73 Sancho-Serra et al found that the desensitized state lasted at least 4 hours, but the authors could not test this beyond 4 hours due to technical difficulties.…”
Section: Rapid Drug Desensitizationmentioning
confidence: 99%
See 3 more Smart Citations